PENGARUH MORALITAS INDIVIDU, KETAATAN ATURAN AKUNTANSI, DAN KESESUAIAN KOMPENSASI TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI (Studi Empiris pada Organisasi Perangkat Daerah Provinsi Riau) - Jack Elsyandi Piotama; Rita Anugerah; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This research aims to determine the effect of individual morality,compliance to accounting rules and compensation suitability to the acceptance oftendency of accounting fraud. The samples of this research are OPD on RiauProvince. The population of this research are 23 agencys. Based on purposivesampling method, the total of final sample are 115 samples. Analysis of data iscarried out using multiple regression method with the aid of SPPS version 17computer program. The result of this research show that individual morality,compliance to accounting rules and compensation suitability are significantinfluence on tendency of accounting fraud.Keywords : Tendency Of Accounting Fraud, Individual Morality, Compliance ToAccounting Rules, Compensation Suitability.